Obstacles to the Prosecution Process of Criminal Acts during the Covid-19 Period at the Belawan State Prosecutor's Office - Jerri Habeahan; Jogi Silalahi; Marolop Butarbutar (IHSA Institute, 2022)
Covid-19 or commonly known as Corona Virus Disease abbreviated as COVID is an infectious disease which due to its rapid spread has had a very large impact on an international scale. The purpose of the study was to find out how the process of prosecuting criminal acts at the Belawan District Attorney's Office during the covid-19 period, to find out the obstacles faced by the prosecutor's office and to find out the efforts made by the prosecutor's office. The research method in analyzing this research uses empirical methods. Namely an analysis of the obstacles to prosecuting criminal acts during the Covid-19 period at the Belawan District Attorney. Results Based on research in the field, the highest crimes are crimes in drug cases, theft and violence.